The first record of the representative of the genus Tenebriella (Cyanobacteria, Oscillatoriales) at Cape Kazantip (the Sea of Azov, Ukraine) - Mikhailyuk, T.I.; Vinogradova, O.M. (M.G. Kholodny Institute of Botany, NAS of Ukraine, 2022)
Studying terrestrial algae of the Kazantip Nature Reserve (Kerch Peninsula) and its environs, a morphologically distinctive homocytic filamentous cyanobacterium with dark coloured trichomes was found in the biological soil crust from the surface of the clay scree. Despite the peculiar coloration and rather large dimensions of the filaments, we failed to identify it even to the genus based on morphological features. Unfortunately, a molecular study of this material was impossible since an attempt to isolate it in the unialgal culture was unsuccessful. The recently described genus Tenebriella Hauerová, Hauer et Kaštovský separated from Oscillatoria sensu lato, has morphological features very close to our material. They include dark colored filaments, trichomes pale-greyish green to purple, slightly constricted at the cross walls, with short cells, gently tapering to the ends, and several last cells of the trichome often yellowish. Morphologically and ecologically Ukrainian record is very close to T. amphibia Hauerová, Hauer et Kaštovský, but is characterized by noticeably thinner trichomes. Morphological description of this species, photomicrographs, information on habitat in Ukraine and ecology, comparison with literature data are given.